Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1136/annrheumdis-2017-211501
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase Jumonji domain-containing protein 3 (JMJD3) regulates fibroblast activation in systemic sclerosis

Abstract: Abstract:Objectives Systemic sclerosis (SSc) fibroblasts remain activated even in the absence of exogenous stimuli. Epigenetic alterations are thought to play a role for this endogenous activation. Trimethylation of histone H3 on lysine 27 (H3K27me3) is regulated by Jumonji domain-containing protein 3 (JMJD3) and ubiquitously transcribed tetratricopeptide repeat on chromosome X (UTX) in a therapeutically targetable manner. The aim of this study was to explore H3K27me3 demethylases as potential targets for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…SSc fibroblasts demonstrate global alterations in methylation, particularly the hypomethylation of genes including ITGA9, ADAM12, COL23A1, COL4A2 MYO1E, and the RUNX family of transcription factors [18]. Functionally, epigenetic alteration of histone demethylases such as MeCP2 and JMJD3 regulate epigenetic modifications on transcription factor promoters and determine fibroblasts' fibrogenic potential [19,20]. The Wnt pathway genes DKK1 and SFRP1 are also hypomethylated in both SSc fibroblasts and peripheral blood mononuclear cells (PBMCs).…”
Section: Epigenetic Programming Of Ssc Fibroblastsmentioning
confidence: 99%
“…SSc fibroblasts demonstrate global alterations in methylation, particularly the hypomethylation of genes including ITGA9, ADAM12, COL23A1, COL4A2 MYO1E, and the RUNX family of transcription factors [18]. Functionally, epigenetic alteration of histone demethylases such as MeCP2 and JMJD3 regulate epigenetic modifications on transcription factor promoters and determine fibroblasts' fibrogenic potential [19,20]. The Wnt pathway genes DKK1 and SFRP1 are also hypomethylated in both SSc fibroblasts and peripheral blood mononuclear cells (PBMCs).…”
Section: Epigenetic Programming Of Ssc Fibroblastsmentioning
confidence: 99%
“…Because the activated phenotype of SSc (myo) fibroblasts persists ex vivo , e.g., during cell culture, epigenetic changes most likely play an important role in this phenotype. For example, recent research has shown that in SSc skin fibroblasts, expression of the histone demethylase Jumonji domain-containing protein 3 (JMJD3) is increased ( 99 ). This histone demethylase removes the so-called H3K27me3 mark from histones, and this mark can repress expression of pro-fibrotic genes such as collagen type I in fibroblasts ( 100 ).…”
Section: On Increased Activity Of Myofibroblasts In Sscmentioning
confidence: 99%
“…Furthermore, pharmacological inhibition of H3K27 trimethylation induces skin fibrosis and aggravates pathology in bleomcyin induced skin fibrosis ( 100 ). A key target which is activated by JMJD3 is Fos-related antigen 2 (Fra-2) ( 99 ). This transcription factor has been identified as an important regulator of extracellular matrix production in skin fibroblasts; transgenic overexpression of Fra-2 results in increased dermal thickness and myofibroblast formation and is a mouse model for SSc ( 101 ), whereas knockdown of Fra-2 reduces both TGFβ- and PDGF-induced collagen production in primary skin fibroblasts of SSc patients ( 102 ).…”
Section: On Increased Activity Of Myofibroblasts In Sscmentioning
confidence: 99%
“…It was indicated that JMJD3 promoted fibroblast activation via enhancing FRA2 expression. Special silencing of JMJD3 inhibited abnormal activation of SSc fibroblasts and exert effective anti-fibrotic effects in mouse models (Bergmann et al 2018). In osteoarthritis, TGF-β enhanced the expression of JMJD3 and increased JMJD3 targeted osteoarthritis (OA)-associated genes, and thus enhanced chondrocyte hypertrophy and matrix destruction, leading to OA progression (Yapp et al 2016).…”
Section: Jmjd3 In Immune Diseasesmentioning
confidence: 99%